2009
DOI: 10.1007/s11060-009-9826-3
|View full text |Cite
|
Sign up to set email alerts
|

Decreased rate of infection in glioblastoma patients with allelic loss of chromosome 10q

Abstract: Introduction Chromosome 10q allelic loss commonly occurs in glioblastoma. Disruption of PTEN, one of three known 10q tumor suppressor genes, affects the immune system by increasing tumor expression of immunosuppressive protein B7-H1 and by increasing tumor release of Th2-inducing cytokines. While the former might impair antitumor cellular immunity, a consideration for immunotherapy, the latter could cause 10q-maintaining tumor patients to experience comparatively higher rates of bacterial infections, a source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…18,19 Three tumor suppressor genes residing on chromosome 10q (ERCC6, PTEN/MMAC1, and DMBT1) have been implicated in the development and progression of several types of neoplasms. [20][21][22] High frequency of allelic loss on chromosome 10q23, where PTEN/MMAC1 gene locates was also reported in phyllodes tumor of the prostate. 8 No tumor suppressor genes have been well defined on chromosome 14, but putative tumor suppressor loci had been mapped by using microsatellite allotyping.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Three tumor suppressor genes residing on chromosome 10q (ERCC6, PTEN/MMAC1, and DMBT1) have been implicated in the development and progression of several types of neoplasms. [20][21][22] High frequency of allelic loss on chromosome 10q23, where PTEN/MMAC1 gene locates was also reported in phyllodes tumor of the prostate. 8 No tumor suppressor genes have been well defined on chromosome 14, but putative tumor suppressor loci had been mapped by using microsatellite allotyping.…”
Section: Discussionmentioning
confidence: 99%
“…The former relies on local cellular immunity mediated by the Th 1 subset of helper T cells, while the latter relies on systemic humoral immunity mediated by the Th 2 subset of helper T cells. [34][35] Past empiric observations reported that patients with GBM who experienced a postoperative cranial wound infection exhibited longer survival. This observation was initially attributed to bacterial lipopolysaccharide (LPS) eliciting a nonspecific immune response which also targets the tumor.…”
Section: The Immunology Of Gbmmentioning
confidence: 99%
“…[40][41][42] The most common genetic alteration in GBM tumors is the loss of heterozygosity of chromosome #10, occurring in 80~95% of these tumors. [34][35][40][41][42] Interestingly, disruption of two of these tumor suppressor genes found on chromosome 10q may mediate a decrease in tumor cell immunogenicity (i.e. DBMT1, PTEN).…”
Section: The Immunology Of Gbmmentioning
confidence: 99%
“…Since these initial pivotal observations, with developing techniques and widespread interest, multiple studies were put forward describing different molecular immunosuppressive mechanisms taking place in GBM cells and microenvironment, claiming these to be the dominant key events (table 1) [1,5] . Unfortunately, things are not as straightforward or simple, and both arms of the immune system are known to be hampered in GBM, as do many other anatomical barriers, micro-environmental conditions and features unique to tumors within the central nervous system, once termed as immune-privileged [27][28] .…”
Section: Anti-apoptosis Upregulation Of Anti-apoptotic Proteins (Iementioning
confidence: 99%